High-barrier inflatable cushion and preparation process thereof
Through the combination and process processing of EVOH and TPU materials, high -resistance inflatable cushions are prepared to solve the deficiencies of traditional inflatable cushions in gas resistance and mechanical properties, and achieve higher gas blockage and mechanical properties.
Patent Information
- Application Number
- CN202411685951.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-23
- Publication Date
- 2025-01-28
AI Technical Summary
The existing inflatable cushions have shortcomings in gas barrier properties and mechanical properties, which are difficult to meet the needs of high-end applications.
By rationally combining EVOH and TPU materials, combine EVOH's gas barrier characteristics and the elasticity and mechanical strength of TPU, to prepare high -resistance inflatable cushions. Specific processes include the delay to prepare the TPU-EVOH composite material, and form airbag molding materials and airbag base materials through steps such as cooling and cooling drying through spraying and cold drying.
On the basis of maintaining good gas blocking performance, it provides stronger mechanical support and higher service life, thereby improving the overall performance of the inflatable cushion.
Smart Images

Figure CN119369775A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of high-barrier inflatable cushions, in particular to a high-barrier inflatable cushion and a preparation process thereof. Background Art
[0002] As the packaging industry's demand for high-performance materials continues to grow, inflatable cushions, as an important protective material, are widely used in electronic products, pharmaceutical packaging, food transportation and other fields. Traditional inflatable cushions are mostly made of polyethylene (PE), polypropylene (PP) and other materials, which usually have certain cushioning and impact resistance, but have obvious deficiencies in gas barrier properties and mechanical properties, which restricts their performance in high-end applications.
[0003] In the prior art, EVOH (ethylene-vinyl acetate copolymer), as a material with excellent gas barrier properties, is often used in food packaging, medical packaging and other fields. EVOH can effectively prevent the penetration of gases such as oxygen and carbon dioxide, and extend the shelf life and storage stability of products. However, although EVOH has excellent gas barrier properties, its own water resistance is poor and it is easily affected by moisture, resulting in a decrease in its barrier properties in a humid environment. In addition, EVOH is very brittle and it is difficult to meet the flexibility and toughness requirements of the inflatable cushion in practical applications. Therefore, it is difficult to take into account both good gas barrier properties and mechanical properties in the inflatable cushion using EVOH alone.
[0004] On the other hand, TPU (thermoplastic polyurethane) materials are widely used in fields requiring higher mechanical properties due to their excellent elasticity, wear resistance and tensile resistance. In the application of inflatable cushions, TPU can provide good cushioning effect and durability, but its gas barrier performance is relatively weak. TPU material itself does not have the superior gas barrier ability like EVOH, resulting in insufficient protection of the inflatable cushion in terms of moisture and oxidation resistance, and cannot effectively deal with the problem of gas permeation after long-term exposure to air. Therefore, the inadequacy of gas barrier properties and mechanical properties of traditional materials makes existing inflatable cushions face challenges in high-demand applications.
[0005] In order to overcome the above problems, the present invention strives to improve the gas barrier performance of the inflatable cushion while enhancing its mechanical properties by reasonably selecting a combination of EVOH and TPU. The gas barrier properties of EVOH combined with the elasticity and mechanical strength of TPU can provide stronger mechanical support and longer service life while maintaining good gas barrier properties, thereby achieving high-performance inflatable cushion materials. Summary of the invention
[0006] The object of the present invention is to provide a high-barrier air-filled cushion and a preparation process thereof, so as to solve the problems raised in the prior art.
[0007] To achieve the above object, the present invention provides the following technical solutions: A preparation process of a high-barrier inflatable cushion comprises the following steps: S1: feeding: unwinding the airbag molding material TPU layer upwards and feeding; S2: Heating: moving the airbag molding material to a heating chamber for heating; S3: Vacuum pressing: After heating, the airbag molding material is moved to the molding chamber, vacuum adsorbed, and pressed to shape; S4: Spray cooling: After the molding is completed, the airbag molding material is moved to the spray chamber for spray cooling; S5: air cooling and drying: after cooling, the airbag forming material is moved to the air drying room for air cooling and drying; S6: Cutting: After drying, the airbag molding material is moved to the cutting area and cut to obtain the airbag semi-finished product; S7: heat sealing: heat sealing a sheet of airbag semi-finished product and a sheet of airbag base material to obtain a high-barrier inflatable cushion; Furthermore, the airbag molding material is formed by laminating a TPU-EVOH composite material and a Lycra fabric, and the airbag base material is formed by laminating a TPU-EVOH composite material and a non-woven fabric.
[0008] Further, in step S2, the heating temperature is 350-400°C and the heating time is 15-30s; Furthermore, in step S3, the vacuum adsorption time is 10-60 seconds, and the pressure setting time is 80-100 seconds; Further, in step S4, the spray pressure during the spray cooling process is 0.2-0.5 MPa, and the spray time is 1-5 s; Furthermore, in step S5, the air-cooling drying time is 50-100 seconds.
[0009] Furthermore, in the airbag molding material, the total thickness of the TPU-EVOH composite material is 0.4-0.8 mm, and the gram weight of the Lycra fabric is 150-230 g / m 2 ; Furthermore, in the airbag base material, the total thickness of the TPU-EVOH composite material is 0.1-0.3 mm, and the gram weight of the non-woven fabric is 60-80 g / m 2 .
[0010] Furthermore, the preparation method of the airbag forming material or the airbag base material comprises the following steps: EVOH material and TPU material are co-extruded by cast film to obtain TPU-EVOH composite material; PUR moisture-curing hot melt adhesive is coated on the EVOH surface of the TPU-EVOH composite material to obtain an adhesive layer, the adhesive layer is heated to 120-140°C, Lycra fabric or non-woven fabric is attached to the EVOH surface, allowed to stand for 24 hours, and cured in an environment of 50-70% humidity and 15-30°C for 4-7 days to obtain an airbag molding material or an airbag base material; the thickness of the TPU material is 0.15-0.8mm, the thickness of the EVOH material is 0.02-0.05mm, and the peel strength of the adhesive layer is 35-60N.
[0011] Furthermore, the EVOH material includes any one of EVOH, EVOH copolymer and EVOH nanocomposite material.
[0012] Furthermore, the preparation method of the EVOH copolymer comprises the following steps: adding (Z)-3-bromo-1-cyclooctene to a mixture of acetone and sodium bicarbonate aqueous solution, heating and refluxing for reaction for 1-1.5 hours, filtering, concentrating the filtrate, extracting with ether, separating the ether phase, drying and concentrating, and vacuum distilling to obtain 3-hydroxy-1-cyclooctene; adding 3-hydroxy-1-cyclooctene and pyridine to dichloromethane, adding acetyl chloride under ice bath conditions, stirring at room temperature for 3-3.5 hours, adding the reaction mixture to a 2 mol / L hydrochloric acid solution, separating the organic phase, extracting the aqueous phase with dichloromethane, washing the combined organic phase with a saturated sodium bicarbonate aqueous solution, drying and concentrating with magnesium sulfate, and vacuum distilling to obtain (Z)-cyclooct-2-ene-1-yl acetate; (Z)-cyclooct-2-ene-1-yl acetate is added to a reaction vessel, toluene is added, degassing is performed using three freeze-pump-thaw cycles, argon is introduced, the reaction is heated to 40-42°C, GRUBBS second-generation catalyst is added, the reaction is kept warm for 24 hours, vinyl ethyl ether is added for quenching, the reaction mixture is added to methanol to separate the polymer, the polymer is added to dichloromethane, the polymer is precipitated again in methanol to purify it, 2,6-di-tert-butyl-p-cresol is added to the polymer and the mixture is dried under vacuum at 70-72°C for 24 hours to obtain a polyolefin monomer, and the polyolefin monomer is hydrogenated and deprotected to obtain an EVOH copolymer.
[0013] Furthermore, the hydrogenation process includes the following steps: adding a polyolefin monomer into a container, adding xylene, 2,6-di-tert-butyl-p-cresol, and tributylamine, stirring evenly, adding p-toluenesulfonyl hydrazide, heating to 140-145° C. for reflux reaction for 8 hours, cooling to room temperature, rotary evaporation, adding the mixed product into methanol for precipitation purification, and placing it at 70° C. for vacuum drying for 24 hours to obtain an intermediate.
[0014] Furthermore, the deprotection process includes the following steps: adding the intermediate to tetrahydrofuran, adding 25wt% sodium methoxide solution, stirring the reaction for 24 hours, adding acidic methanol until the reaction pH is acidic, filtering, washing the filtrate with methanol, adding methanol to precipitate and purify, adding hexafluoroisopropanol to the polymer and heating it to 50°C to dissolve, placing it at 70°C and vacuum drying for 24 hours to obtain EVOH copolymer.
[0015] Furthermore, the method for preparing the second-generation GRUBBS catalyst comprises the following steps: adding the second-generation GRUBBS catalyst into a container, evacuating the container, introducing argon gas, adding toluene, and stirring uniformly.
[0016] Furthermore, in the preparation process of the 3-hydroxy-1-cyclooctene, the concentration of the sodium bicarbonate aqueous solution is 0.03 mol / L; in the preparation process of (Z)-cyclooct-2-ene-1-yl acetate, the molar ratio of 3-hydroxy-1-cyclooctene: pyridine: acetyl chloride is 0.1:0.15:0.15; in the preparation process of the EVOH copolymer, the molar ratio of (Z)-cyclooct-2-ene-1-yl acetate: GRUBBS second-generation catalyst is 29.7:0.0074.
[0017] Furthermore, the preparation method of the EVOH nanocomposite material comprises the following steps: The mixed nanofiller was added into deionized water, ultrasonically dispersed, a Tris-HCl buffer solution was added, stirred evenly, a dopamine hydrochloride aqueous solution was added, stirred for reaction for 24 hours, centrifuged, the solid product was collected, and freeze-dried to obtain a dopamine-modified mixed nanofiller; The EVOH copolymer is added to N,N-dimethylformamide, heated to 70-72°C and stirred evenly, cooled to room temperature, dopamine-modified mixed nanofiller and boric acid aqueous solution are added in sequence, ultrasonically dispersed, the mixture is added to a polytetrafluoroethylene container, heated to 70-72°C, vacuum heat treated for 6-7h, hydrazine vapor treated, and vacuum dried at 50-70°C to obtain an EVOH nanocomposite material; Furthermore, the hybrid nanofiller is prepared from 3-aminopropyltriethoxysilane-modified MXene and graphene oxide.
[0018] Furthermore, during the preparation of the dopamine modified mixed nanofiller, the pH of the Tris-HCl buffer solution is 8.5; during the preparation of the EVOH nanocomposite material, the amount of dopamine modified mixed nanofiller added is 5-10wt% of the mass of the EVOH copolymer, and the amount of boric acid added is 5-20wt% of the mass of the EVOH copolymer.
[0019] Furthermore, the preparation method of the hybrid nanofiller comprises the following steps: adding lithium fluoride to a 9M hydrochloric acid solution, stirring evenly, adding titanium aluminum carbide powder under ice bath conditions, heating to 35-36°C for reaction for 24 hours, washing the reaction suspension with deionized water, centrifuging, collecting the precipitate, washing the precipitate to a neutral pH, ultrasonically dispersing the precipitate in deionized water, centrifuging, collecting the supernatant, purging with nitrogen, and freeze-drying to obtain MXene; MXene was added to an ethanol aqueous solution, ultrasonically dispersed under a nitrogen atmosphere, the pH of the suspension was adjusted to 3-4, 3-aminopropyltriethoxysilane was added, the reaction was stirred at room temperature for 24 hours, the suspension was washed with ethanol, centrifuged, and freeze-dried to obtain modified MXene; the modified MXene and graphene oxide were added to N,N-dimethylformamide, ultrasonically dispersed under a nitrogen atmosphere, carbodiimide, 1-hydroxybenzotriazole hydrate, and N,N-diisopropylethylamine were added, the reaction was carried out under a nitrogen atmosphere for 24 hours, the product was washed with N,N-dimethylformamide and deionized water, and freeze-dried to obtain a mixed nanofiller.
[0020] Furthermore, in the preparation process of the MXene, the mass ratio of lithium fluoride: titanium aluminum carbide is 1.95:2.9; in the preparation process of the modified MXene, the mass ratio of MXene: 3-aminopropyltriethoxysilane is 1:2; in the preparation process of the mixed nanofiller, the mass ratio of modified MXene: graphene oxide: carbodiimide: 1-hydroxybenzotriazole hydrate: N,N-diisopropylethylamine is 125:125:67:67:1.
[0021] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention realizes the controllable polymerization of cyclic olefins by means of ring-opening metathesis polymerization of (Z)-3-bromo-1-cyclooctene, and then performs hydrogenation and deprotection processes to prepare an EVOH copolymer with regional regularity of molecular structure. Different from the traditional commercially available EVOH (EVOH-44 has 44 mol% ethylene units, and EVOH-32 has 32 mol% ethylene units), the EVOH copolymer prepared by the present invention has 75 mol% ethylene units, and the arrangement has the characteristics of linearity and high regularity, which can provide excellent gas barrier properties for the inflatable cushion.
[0022] 2. In order to further improve the gas barrier performance and mechanical properties of the inflatable cushion based on the above-mentioned EVOH copolymer, the self-made dopamine-modified mixed nanofiller is added to the EVOH copolymer and boric acid is added as a crosslinking agent to induce crosslinking. Boric acid ions are used to induce crosslinking between the EVOH copolymer and the dopamine-modified mixed nanofiller, and the interface interaction between the filler and the matrix resin is enhanced. A crosslinking network is formed between the EVOH copolymer, boric acid and the dopamine-modified mixed nanofiller. At the same time, during the heat treatment crosslinking process, the dopamine-modified mixed nanofiller and the dopamine-modified mixed nanofiller can also be crosslinked together through the action of boric acid, so that the distance between the lamella filler in the horizontal and vertical directions is closer, achieving the effect of increasing the complexity of the gas channel. The introduction of the composite filler provides the inflatable cushion with excellent gas barrier performance, mechanical properties and thermal stability.
[0023] 3. The hybrid nanofiller in the dopamine-modified hybrid nanofiller of the present invention is prepared by covalently bonding MXene and graphene oxide through 3-aminopropyltriethoxysilane. The mixing gap of the hybrid nanofiller is larger than that of the original MXene and graphene oxide. The purpose is to facilitate the subsequent dopamine modification and then the introduction of boric acid ions to prepare for cross-linking with the EVOH copolymer, so that the subsequent cross-linking network is tighter, the interface interaction is enhanced, and the gas barrier properties and mechanical properties are improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a schematic diagram of the steps of preparing a high-barrier air cushion according to the present invention; Figure 2 This is a schematic diagram of the structure of a 36-bubble seat cushion of a high-barrier inflatable cushion of the present invention; Figure 3 This is a schematic diagram of the structure of a 49-bubble seat cushion of a high-barrier inflatable cushion of the present invention; Figure 4 It is a schematic structural diagram of an anti-bedsore pad of a high-barrier inflatable pad of the present invention; Figure 5 It is a schematic diagram of the shoulder strap structure of a high-barrier inflatable cushion of the present invention; Figure 6 This is a schematic structural diagram of a bicycle cushion with a high-barrier inflatable cushion according to the present invention; Figure 7 It is a schematic diagram of the double-sided seat cushion structure of a high-barrier inflatable cushion of the present invention; Figure 8 The present invention is a schematic structural diagram of an electric massage seat cushion with a high-barrier inflatable cushion. DETAILED DESCRIPTION
[0025] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] In the following embodiments, the specifications of common commercially available EVOH: ethylene content 32 mol%, purchased from Sigma-Aldrich; TPU model: HF-1380A, purchased from Huafeng Group; Lycra fabric purchased from Lycra Company; non-woven fabric purchased from Shandong Huaye Nonwoven Fabric Co., Ltd.; PUR moisture-curing hot melt adhesive model: 3930, purchased from Kane Chemical; (Z)-3-bromo-1-cyclooctene CAS: 7422-06-2; graphene oxide purchased from Sigma-Aldrich; dopamine hydrochloride purchased from Aladdin; the remaining raw materials are commercially available.
[0027] In the following examples, the preparation method of the hybrid nanofiller comprises the following steps: adding 1.95 g of lithium fluoride to 60 mL of 9 M hydrochloric acid solution, stirring evenly, adding 2.9 g of titanium carbide aluminum powder under ice bath conditions, heating to 35° C. to react for 24 h, washing the reaction suspension with deionized water, centrifuging, collecting the precipitate, washing the precipitate to a neutral pH, ultrasonically dispersing the precipitate in deionized water, centrifuging, collecting the supernatant, purging with nitrogen, and freeze-drying to obtain MXene; 100 mg of MXene was added to an ethanol-water solution with a volume ratio of 9:1, and ultrasonically dispersed under a nitrogen atmosphere. The pH of the suspension was adjusted to 3, and 200 mg of 3-aminopropyltriethoxysilane was added. The reaction was stirred at room temperature for 24 hours, and the suspension was washed with ethanol. The suspension was centrifuged and freeze-dried to obtain modified MXene. 125 mg of modified MXene and 125 mg of graphene oxide were added to 50 mL of N, N-dimethylformamide, and ultrasonically dispersed under a nitrogen atmosphere. 67 mg of carbodiimide, 67 mg of 1-hydroxybenzotriazole hydrate, and 1 g of N, N-diisopropylethylamine were added. The reaction was carried out under a nitrogen atmosphere for 24 hours. The product was washed with N, N-dimethylformamide and deionized water, and freeze-dried to obtain a mixed nanofiller.
[0028] Example 1: See Figure 1 ,A preparation process of a high barrier inflatable cushion comprises the following steps: S1: feeding: unwinding the airbag forming material TPU layer facing upwards, feeding; S2: Heating: Move the airbag molding material to the heating chamber and heat at 130°C for 15s; S3: Vacuum pressing: After heating, the airbag molding material is moved to the molding chamber, vacuum adsorbed for 10 seconds, and pressed for 80 seconds; S4: Spray cooling: After the molding is completed, the airbag molding material is moved to the spray chamber for spray cooling; 0.2MPa spray pressure, spray cooling for 1s; S5: air cooling and drying: after cooling, the airbag molding material is moved to the air drying room and air-cooled and dried for 50 seconds; S6: Cutting: After drying, the airbag molding material is moved to the cutting area and cut to obtain the airbag semi-finished product; S7: heat sealing: heat sealing a sheet of airbag semi-finished product and a sheet of airbag base material to obtain a high-barrier air cushion.
[0029] The preparation method of an airbag molding material comprises the following steps: co-extruding an EVOH material and a TPU material by casting to obtain a TPU-EVOH composite material; coating a PUR moisture-curing hot melt adhesive on the EVOH surface of the TPU-EVOH composite material to obtain a bonding layer, heating the bonding layer to 120° C., laminating a Lycra fabric on the EVOH surface, standing for 24 hours, and curing for 4 days in an environment of 50% humidity and 20° C. to obtain an airbag molding material; the total thickness of the TPU-EVOH composite material is 0.4 mm, and the gram weight of the Lycra fabric is 150 g / m 2 .
[0030] The preparation method of the airbag base material comprises the following steps: co-extruding EVOH material and TPU material by casting to obtain TPU-EVOH composite material; coating PUR moisture-curing hot melt adhesive on the EVOH surface of the TPU-EVOH composite material to obtain an adhesive layer, heating the adhesive layer to 120°C, laminating a non-woven fabric on the EVOH surface, standing for 24 hours, and curing for 4 days in an environment of 50% humidity and 20°C to obtain the airbag base material; the total thickness of the TPU-EVOH composite material is 0.1 mm, and the gram weight of the non-woven fabric is 60 g / m 2 .
[0031] In the preparation process of the airbag molding material and the airbag base material, the EVOH material is common commercially available EVOH.
[0032] Example 2: A process for preparing a high-barrier inflatable cushion: In the preparation process of the airbag molding material and the airbag base material, the EVOH material is an EVOH copolymer; The preparation process of EVOH copolymer comprises the following steps: adding 25g (Z)-3-bromo-1-cyclooctene to a mixture of 200mL acetone and 100mL 0.03mol / L sodium bicarbonate aqueous solution, heating and refluxing for reaction for 1h, filtering, concentrating the filtrate, extracting with ether, separating the ether phase, drying and concentrating, and vacuum distilling to obtain 3-hydroxy-1-cyclooctene; adding 0.1mol 3-hydroxy-1-cyclooctene and 0.15mol pyridine to 200mL dichloromethane, adding 0.15mol acetyl chloride under ice bath condition, stirring at room temperature for 3h, adding the reaction mixture to 2mol / L hydrochloric acid solution, separating the organic phase, extracting the aqueous phase with dichloromethane, washing the combined organic phase with saturated sodium bicarbonate aqueous solution, drying and concentrating with magnesium sulfate, and vacuum distilling to obtain (Z)-cyclooct-2-ene-1-yl acetate; 29.7 mmol (Z)-cyclooct-2-ene-1-yl acetate was added to a reaction vessel, 20 mL toluene was added, degassed using 3 freeze-pump-thaw cycles, argon was introduced, heated to 40°C, 0.0074 mmol GRUBBS second-generation catalyst was added, the reaction was kept warm for 24 hours, 1 mL of vinyl ethyl ether was added for quenching, the reaction mixture was added to methanol to separate the polymer, the polymer was added to dichloromethane, the polymer was precipitated again in methanol to purify it, 2 mg 2,6-di-tert-butyl-p-cresol was added to the polymer and dried under vacuum at 70°C for 24 hours to obtain a polyolefin monomer, and the polyolefin monomer was hydrogenated and deprotected to obtain an EVOH copolymer.
[0033] The hydrogenation process comprises the following steps: adding 40.5 mmol of polyolefin monomer into a container, adding 250 mL of xylene, 80 mg of 2,6-di-tert-butyl-p-cresol, and 29 mL of tributylamine, stirring evenly, adding p-toluenesulfonyl hydrazide, heating to 140° C. for reflux reaction for 8 hours, cooling to room temperature, rotary evaporation, adding the mixed product into methanol for precipitation purification, placing it at 70° C. for vacuum drying for 24 hours, and obtaining an intermediate.
[0034] The deprotection process comprises the following steps: adding 6.2 g of the intermediate into tetrahydrofuran, adding 16 g of a 25 wt% sodium methoxide solution, stirring the reaction for 24 h, adding acidic methanol until the reaction pH is acidic, filtering, washing the filtrate with methanol, adding hexafluoroisopropanol to the polymer and heating it to 50° C. to dissolve it, adding methanol to precipitate and purify it, placing it at 70° C. and vacuum drying it for 24 h to obtain an EVOH copolymer.
[0035] The method for preparing the GRUBBS second-generation catalyst comprises the following steps: adding 0.0074 mmol of the GRUBBS second-generation catalyst into a container, evacuating the container, introducing argon gas, adding 1 mL of toluene, and stirring the container evenly.
[0036] The remaining steps are the same as those in Example 1.
[0037] Example 3: A process for preparing a high-barrier inflatable cushion: In the process of preparing the airbag molding material and the airbag base material, the EVOH material is an EVOH nanocomposite material; The preparation method of EVOH nanocomposite material comprises the following steps: adding 100 mg of mixed nanofiller into 250 mL of deionized water, ultrasonically dispersing, adding 100 mL of Tris-HCl buffer solution, stirring evenly, adding 100 mL of dopamine hydrochloride aqueous solution, stirring and reacting for 24 hours, centrifuging, collecting solid products, and freeze-drying to obtain dopamine modified mixed nanofiller; Add 100g EVOH copolymer to N,N-dimethylformamide, heat to 70°C and stir evenly, cool to room temperature, add 5g dopamine-modified mixed nanofiller and boric acid aqueous solution containing 5g boric acid in sequence, and disperse ultrasonically. Add the mixture into a polytetrafluoroethylene container, heat to 70°C and perform vacuum heat treatment for 6h, treat with hydrazine vapor, and dry in vacuum at 50°C to obtain an EVOH nanocomposite material.
[0038] The remaining steps are the same as those in Example 1.
[0039] Example 4: A process for preparing a high-barrier inflatable cushion: In the process of preparing the airbag forming material and the airbag base material, the EVOH material is an EVOH nanocomposite material; The preparation method of EVOH nanocomposite material comprises the following steps: adding 100 mg of mixed nanofiller into 250 mL of deionized water, ultrasonically dispersing, adding 100 mL of Tris-HCl buffer solution, stirring evenly, adding 100 mL of dopamine hydrochloride aqueous solution, stirring and reacting for 24 hours, centrifuging, collecting solid products, and freeze-drying to obtain dopamine modified mixed nanofiller; Add 100g EVOH copolymer to N,N-dimethylformamide, heat to 70°C and stir evenly, cool to room temperature, add 7g dopamine-modified mixed nanofiller and boric acid aqueous solution containing 15g boric acid in sequence, and disperse ultrasonically. Add the mixture into a polytetrafluoroethylene container, heat to 70°C and perform vacuum heat treatment for 6h, treat with hydrazine vapor, and dry in vacuum at 50°C to obtain an EVOH nanocomposite material.
[0040] The remaining steps are the same as those in Example 1.
[0041] Example 5: A process for preparing a high-barrier inflatable cushion: In the process of preparing the airbag molding material and the airbag base material, the EVOH material is an EVOH nanocomposite material; The preparation method of EVOH nanocomposite material comprises the following steps: adding 100 mg of mixed nanofiller into 250 mL of deionized water, ultrasonically dispersing, adding 100 mL of Tris-HCl buffer solution, stirring evenly, adding 100 mL of dopamine hydrochloride aqueous solution, stirring and reacting for 24 hours, centrifuging, collecting solid products, and freeze-drying to obtain dopamine modified mixed nanofiller; Add 100g EVOH copolymer to N,N-dimethylformamide, heat to 70°C and stir evenly, cool to room temperature, add 7g dopamine modified mixed nanofiller and boric acid aqueous solution containing 20g boric acid in sequence, ultrasonically disperse, add the mixture into a polytetrafluoroethylene container, heat to 70°C and vacuum heat treat for 6h, treat with hydrazine vapor, and vacuum dry at 50°C to obtain EVOH nanocomposite material.
[0042] The remaining steps are the same as those in Example 1.
[0043] Example 6: A process for preparing a high-barrier inflatable cushion: In the process of preparing the airbag molding material and the airbag base material, the EVOH material is an EVOH nanocomposite material; The preparation method of EVOH nanocomposite material comprises the following steps: adding 100 mg of mixed nanofiller into 250 mL of deionized water, ultrasonically dispersing, adding 100 mL of Tris-HCl buffer solution, stirring evenly, adding 100 mL of dopamine hydrochloride aqueous solution, stirring and reacting for 24 hours, centrifuging, collecting solid products, and freeze-drying to obtain dopamine modified mixed nanofiller; Add 100g EVOH copolymer to N,N-dimethylformamide, heat to 70°C and stir evenly, cool to room temperature, add 10g dopamine modified mixed nanofiller and boric acid aqueous solution containing 20g boric acid in sequence, ultrasonically disperse, add the mixture into a polytetrafluoroethylene container, heat to 70°C and vacuum heat treat for 6h, treat with hydrazine vapor, and vacuum dry at 50°C to obtain EVOH nanocomposite material.
[0044] The remaining steps are the same as those in Example 1.
[0045] Example 7: A preparation process of a high barrier air cushion: A 36-bubble cushion prepared according to the method disclosed in Example 1, such as Figure 2 As shown. The 36-bubble cushion uses a mold with 36 airbag positions to vacuum-absorb and press the airbag molding material. After cutting and heat-sealing, a cloth cushion layer is added to the bottom surface for hemming and sewing. The two corner airbags are provided with built-in inflation nozzles and built-in deflation nozzles on the back. Due to the high barrier properties of the airbag material of the present invention, the 36-bubble cushion can reduce the inflation operation during use, is comfortable to use, and has a long service life.
[0046] Example 8: A process for preparing a high barrier air cushion: A 49-bubble cushion prepared according to the method disclosed in Example 1, such as Figure 3 The structure and performance of the 49-bubble cushion are similar to those of Example 7, with more, smaller and flatter airbags, and a larger contact surface with the human body during use, bringing a different use experience. It is equipped with a built-in inflation nozzle and a built-in deflation nozzle. Due to the high barrier properties of the airbag material, the inflation operation can be reduced during use, and the service life is long.
[0047] Example 9: A preparation process of a high-barrier inflatable pad: An anti-bedsore pad prepared according to the method disclosed in Example 1 is as follows: Figure 4 As shown. The airbags of the anti-bedsore pad are arranged to meet the needs of bedsore patients or those who need to prevent bedsores, which can effectively improve the comfort of users. It is equipped with a built-in inflation nozzle and a built-in deflation nozzle. Due to the high barrier properties of the airbag material, the inflation operation can be reduced during use, and the service life is long.
[0048] Example 10: A process for preparing a high barrier inflatable cushion: The shoulder strap prepared according to the method disclosed in Example 1 is as follows: Figure 5 The shoulder strap is used for the shoulder strap of a load-bearing backpack. The airbag is a closed type without an inflation nozzle. Due to the high barrier properties of the airbag material, it has a long service life.
[0049] Example 11: A process for preparing a high barrier inflatable cushion: A bicycle cushion prepared according to the method disclosed in Example 1, such as Figure 6 The shape and airbag layout of the bicycle mat are designed according to the needs of riders. The back of the top airbag is provided with a built-in inflation and deflation nozzle. Due to the high barrier property of the airbag material, the inflation operation can be reduced during use, and the service life is long.
[0050] Example 10: A preparation process of a high barrier air cushion: A double-sided cushion prepared according to the method disclosed in Example 1, such as Figure 7 As shown. The double-sided cushion is made by heat-sealing two identical airbag semi-finished products after vacuum adsorption and pressure shaping of the airbag molding material. The backs of the two airbags in the middle of the top edge are respectively provided with built-in inflation nozzles and built-in deflation nozzles. Due to the high barrier properties of the airbag material, the inflation operation can be reduced during use, and the service life is long.
[0051] Example 11: A process for preparing a high-barrier air cushion: An electric massage cushion prepared according to the method disclosed in Example 1 is as follows: Figure 8 The electric massage cushion is also provided with an electric massager inside the airbag, and due to the high barrier property of the airbag material, the service life is long.
[0052] Comparative Example 1: A process for preparing a high-barrier inflatable cushion: In the process of preparing the airbag molding material and the airbag base material, the EVOH material is an EVOH nanocomposite material; The preparation method of EVOH nanocomposite material comprises the following steps: adding 100 mg of graphene oxide to 250 mL of deionized water, ultrasonically dispersing, adding 100 mL of Tris-HCl buffer solution, stirring evenly, adding 100 mL of dopamine hydrochloride aqueous solution, stirring and reacting for 24 hours, centrifuging, collecting solid products, freeze-drying, and obtaining dopamine-modified mixed nanofiller; Add 100g EVOH copolymer to N,N-dimethylformamide, heat to 70°C and stir evenly, cool to room temperature, add 5g dopamine-modified mixed nanofiller and boric acid aqueous solution containing 5g boric acid in sequence, and disperse ultrasonically. Add the mixture into a polytetrafluoroethylene container, heat to 70°C and perform vacuum heat treatment for 6h, treat with hydrazine vapor, and dry in vacuum at 50°C to obtain an EVOH nanocomposite material.
[0053] The remaining steps are the same as those in Example 1.
[0054] Comparative Example 2: A process for preparing a high-barrier inflatable cushion: In the process of preparing the airbag molding material and the airbag base material, the EVOH material is an EVOH nanocomposite material; The preparation method of EVOH nanocomposite material comprises the following steps: adding 100 mg MXene into 250 mL deionized water, ultrasonically dispersing, adding 100 mL Tris-HCl buffer solution, stirring evenly, adding 100 mL dopamine hydrochloride aqueous solution, stirring and reacting for 24 hours, centrifuging, collecting solid products, freeze-drying, and obtaining dopamine modified mixed nanofiller; Add 100g EVOH copolymer to N,N-dimethylformamide, heat to 70°C and stir evenly, cool to room temperature, add 5g dopamine-modified mixed nanofiller and boric acid aqueous solution containing 5g boric acid in sequence, and disperse ultrasonically. Add the mixture into a polytetrafluoroethylene container, heat to 70°C and perform vacuum heat treatment for 6h, treat with hydrazine vapor, and dry in vacuum at 50°C to obtain an EVOH nanocomposite material.
[0055] The remaining steps are the same as those in Example 1.
[0056] Comparative Example 3: A process for preparing a high-barrier inflatable cushion: In the process of preparing the airbag molding material and the airbag base material, the EVOH material is an EVOH nanocomposite material; The preparation method of EVOH nanocomposite material comprises the following steps: adding 100 mg of mixed nanofiller into 250 mL of deionized water, ultrasonically dispersing, adding 100 mL of Tris-HCl buffer solution, stirring evenly, adding 100 mL of dopamine hydrochloride aqueous solution, stirring and reacting for 24 hours, centrifuging, collecting solid products, and freeze-drying to obtain dopamine modified mixed nanofiller; Add 100g EVOH copolymer to N,N-dimethylformamide, heat to 70°C and stir evenly, cool to room temperature, add 5g dopamine modified mixed nanofiller in turn, ultrasonically disperse, add the mixture into a polytetrafluoroethylene container, heat to 70°C for vacuum heat treatment for 6h, treat with hydrazine vapor, and vacuum dry at 50°C to obtain EVOH nanocomposite material.
[0057] The remaining steps are the same as in Example 1 Experiment: Barrier performance test: The TPU-EVOH composite materials prepared in the above Examples 1-6 and Comparative Examples 1-3 were used as test materials. The test materials were extruded to a thickness of 0.1 mm, a length and a width of 200 mm × 200 mm. The barrier performance was tested according to GB / T1038.1-2022. Experimental parameters: Test area 38.49 cm 2 , barrier property ≥1, upper chamber purge replacement time 607s, upper chamber gas pressure 9.898×10 4 Pa, the degassing time of the lower chamber is 60s, and the degassing time of the upper and lower chambers is 12h. The quality of the barrier performance is judged by the gas permeation amount.
[0058] Mechanical property test: The TPU-EVOH composite materials prepared in the above Examples 1-6 and Comparative Examples 1-3 were used as test materials and tested using a universal testing machine at a tensile rate of 50 mm / min.
[0059] The experimental data are shown in Table 1 below.
[0060] Table 1 High barrier air cushion raw material performance test data table
[0061] Conclusion: The high-barrier air cushion raw material prepared by the present invention has excellent barrier properties and mechanical properties.
[0062] Comparative Example 1 uses graphene oxide to replace the mixed nanofiller, resulting in reduced barrier properties and mechanical properties.
[0063] Comparative Example 2 uses MXene to replace the mixed nanofiller, resulting in reduced barrier properties and mechanical properties.
[0064] In Comparative Example 3, no boric acid aqueous solution was added, resulting in reduced barrier properties and mechanical properties.
[0065] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A process for preparing a high barrier air cushion, characterized in that: The following steps are involved: S1: Feeding: Unwind the airbag molding material TPU layer with the roll facing upwards and feed the material; S2: Heating: moving the airbag molding material to a heating chamber for heating; S3: Vacuum pressing: After heating, the airbag molding material is moved to the molding chamber, vacuum adsorbed, and pressed to shape; S4: Spray cooling: After the molding is completed, the airbag molding material is moved to the spray chamber for spray cooling; S5: air cooling and drying: after cooling, the airbag forming material is moved to the air drying room for air cooling and drying; S6: Cutting: After drying, the airbag molding material is moved to the cutting area and cut to obtain the airbag semi-finished product; S7: heat sealing: heat sealing a sheet of airbag semi-finished product and a sheet of airbag base material to obtain a high-barrier inflatable cushion; The airbag molding material is made of TPU-EVOH composite material and Lycra fabric, and the airbag base material is made of TPU-EVOH composite material and non-woven fabric.
2. The process for preparing a high barrier inflatable cushion according to claim 1, characterized in that: In step S2, the heating temperature is 350-400°C and the heating time is 15-30s; in step S3, the vacuum adsorption time is 10-60s and the pressure setting time is 80-100s; in step S4, the spray pressure during the spray cooling process is 0.2-0.5MPa and the spray time is 1-5s; in step S5, the air cooling and drying time is 50-100s.
3. A high barrier inflatable cushion, characterized in that: In the airbag molding material, the total thickness of TPU-EVOH composite material is 0.4-0.8mm, and the gram weight of Lycra fabric is 150-230g / m 2 In the airbag base material, the total thickness of the TPU-EVOH composite material is 0.1-0.3mm, and the weight of the non-woven fabric is 60-80g / m 2 .
4. A high barrier inflatable cushion according to claim 3, characterized in that: The preparation method of the airbag forming material or the airbag base material comprises the following steps: EVOH material and TPU material are co-extruded by cast film to obtain TPU-EVOH composite material; PUR moisture-curing hot melt adhesive is coated on the EVOH surface of the TPU-EVOH composite material to obtain an adhesive layer, the adhesive layer is heated to 120-140°C, Lycra fabric or non-woven fabric is attached to the EVOH surface, allowed to stand for 24 hours, and cured in an environment of 50-70% humidity and 15-30°C for 4-7 days to obtain an airbag molding material or an airbag base material; the thickness of the TPU material is 0.15-0.8mm, the thickness of the EVOH material is 0.02-0.05mm, and the peel strength of the adhesive layer is 35-60N.
5. A high barrier inflatable cushion according to claim 4, characterized in that: The EVOH material includes any one of EVOH, EVOH copolymer and EVOH nanocomposite material; the preparation method of EVOH copolymer includes the following steps: adding (Z)-3-bromo-1-cyclooctene to a mixture of acetone and sodium bicarbonate aqueous solution, heating and refluxing for reaction for 1-1.5h, filtering, concentrating the filtrate, extracting with ether, separating the ether phase, drying and concentrating, and vacuum distilling to obtain 3-hydroxy-1-cyclooctene; adding 3-hydroxy-1-cyclooctene and pyridine to dichloromethane, adding acetyl chloride under ice bath condition, stirring at room temperature for 3-3.5h, adding the reaction mixture to 2mol / L hydrochloric acid solution, separating the organic phase, extracting the aqueous phase with dichloromethane, washing the combined organic phase with saturated sodium bicarbonate aqueous solution, drying and concentrating with magnesium sulfate, and vacuum distilling to obtain (Z)-cyclooct-2-ene-1-yl acetate; (Z)-cyclooct-2-ene-1-yl acetate is added to a reaction vessel, toluene is added, degassing is performed using three freeze-pump-thaw cycles, argon is introduced, the reaction is heated to 40-42°C, GRUBBS second-generation catalyst is added, the reaction is kept warm for 24 hours, vinyl ethyl ether is added for quenching, the reaction mixture is added to methanol to separate the polymer, the polymer is added to dichloromethane, the polymer is precipitated again in methanol to purify it, 2,6-di-tert-butyl-p-cresol is added to the polymer and the mixture is dried under vacuum at 70-72°C for 24 hours to obtain a polyolefin monomer, and the polyolefin monomer is hydrogenated and deprotected to obtain an EVOH copolymer.
6. A high barrier inflatable cushion according to claim 5, characterized in that: During the preparation of 3-hydroxy-1-cyclooctene, the concentration of the sodium bicarbonate aqueous solution was 0.03 mol / L; during the preparation of (Z)-cyclooct-2-ene-1-yl acetate, the molar ratio of 3-hydroxy-1-cyclooctene: pyridine: acetyl chloride was 0.1:0.15:0.15; during the preparation of EVOH copolymer, the molar ratio of (Z)-cyclooct-2-ene-1-yl acetate: GRUBBS second-generation catalyst was 29.7:0.0074.
7. A high barrier inflatable cushion according to claim 5, characterized in that: The preparation method of EVOH nanocomposite material comprises the following steps: The mixed nanofiller was added into deionized water, ultrasonically dispersed, a Tris-HCl buffer solution was added, stirred evenly, a dopamine hydrochloride aqueous solution was added, stirred for reaction for 24 hours, centrifuged, the solid product was collected, and freeze-dried to obtain a dopamine-modified mixed nanofiller; The EVOH copolymer is added to N,N-dimethylformamide, heated to 70-72°C and stirred evenly, cooled to room temperature, dopamine-modified mixed nanofiller and boric acid aqueous solution are added in sequence, ultrasonically dispersed, the mixture is added to a polytetrafluoroethylene container, heated to 70-72°C, vacuum heat treated for 6-7h, hydrazine vapor treated, and vacuum dried at 50-70°C to obtain an EVOH nanocomposite material; The hybrid nanofiller is prepared from MXene modified by 3-aminopropyltriethoxysilane and graphene oxide.
8. A high barrier inflatable cushion according to claim 7, characterized in that: During the preparation of dopamine modified mixed nanofillers, the pH of the Tris-HCl buffer solution is 8.5; during the preparation of EVOH nanocomposites, the amount of dopamine modified mixed nanofillers added is 5-10wt% of the mass of the EVOH copolymer, and the amount of boric acid added is 5-20wt% of the mass of the EVOH copolymer.
9. The high barrier inflatable cushion according to claim 5, characterized in that: The preparation method of the hybrid nanofiller comprises the following steps: adding lithium fluoride to a 9M hydrochloric acid solution, stirring evenly, adding titanium aluminum carbide powder under ice bath conditions, heating to 35-36° C. for reaction for 24 hours, washing the reaction suspension with deionized water, centrifuging, collecting the precipitate, washing the precipitate to a neutral pH, ultrasonically dispersing the precipitate in deionized water, centrifuging, collecting the supernatant, purging with nitrogen, and freeze-drying to obtain MXene; MXene was added to an ethanol aqueous solution, ultrasonically dispersed under a nitrogen atmosphere, the pH of the suspension was adjusted to 3-4, 3-aminopropyltriethoxysilane was added, the reaction was stirred at room temperature for 24 hours, the suspension was washed with ethanol, centrifuged, and freeze-dried to obtain modified MXene; the modified MXene and graphene oxide were added to N,N-dimethylformamide, ultrasonically dispersed under a nitrogen atmosphere, carbodiimide, 1-hydroxybenzotriazole hydrate, and N,N-diisopropylethylamine were added, the reaction was carried out under a nitrogen atmosphere for 24 hours, the product was washed with N,N-dimethylformamide and deionized water, and freeze-dried to obtain a mixed nanofiller.
10. A high barrier inflatable cushion according to claim 9, characterized in that: During the preparation of MXene, the mass ratio of lithium fluoride: titanium aluminum carbide is 1.95:2.9; during the preparation of modified MXene, the mass ratio of MXene: 3-aminopropyltriethoxysilane is 1:2; during the preparation of mixed nanofillers, the mass ratio of modified MXene: graphene oxide: carbodiimide: 1-hydroxybenzotriazole hydrate: N,N-diisopropylethylamine is 125:125:67:67:1.
Citation Information
Cited By
High-barrier inflatable cushion and preparation process therefor
WO2026108031A1